Research progress on human infection with avian influenza H7N9 - Wu, Xiaoxin (Front Med, 2020)
Since the first case of novel H7N9 infection was reported, China has experienced five epidemics of H7N9. During the fifth wave, a highly pathogenic H7N9 strain emerged. Meanwhile, the H7N9 virus continues to accumulate mutations, and its affinity for the human respiratory epithelial sialic acid 2–6 receptor has increased. Therefore, a pandemic is still possible. In the past 6 years, we have accumulated rich experience in dealing with H7N9, especially in terms of virus tracing, epidemiological research, key site mutation monitoring, critical disease mechanisms, clinical treatment, and vaccine development. In the research fields above, significant progress has been made to effectively control the spread of the epidemic and reduce the fatality rate. To fully document the research progress concerning H7N9, we reviewed the clinical and epidemiological characteristics of H7N9, the key gene mutations of the virus, and H7N9 vaccine, thus providing a scientific basis for further monitoring and prevention of H7N9 influenza epidemics. ELECTRONIC SUPPLEMENTARY MATERIAL: Supplementary material is available in the online version of this article at 10.1007/s11684-020-0739-z and is accessible for authorized users.